Career Aspirations of Final Year Diploma in Librarianship Students in the University of Ghana, Legon - Fosu, V.K. (Ghana Library Journal, 2008)
This study examines career aspirations of final year diploma in librarianship students at the University of Ghana, Legon. The questionnaire administered covered the demographic factors, educational background, work experience, career aspirations and further education plans of the respondents. The findings of the study indicate that majority of the students are interested in the information profession but the number of students not interested in the profession is quite Significant; they are rather interested in areas like banking, public relations, computer engineering, home science, military service among others. It has been suggested that students who are not interested in information management and related fields should be weeded out through a rigorous interviewing session since the mandate of the Department of Information Studies is to train information professionals.